ANALYSIS OF LEARNING PROBLEMS OF NUMERIC LITERACY AND CHARACTER FOR ELEMENTARY SCHOOL STUDENTS - Ni Kadek Anggun Wahyuni; Nyoman Ayu Putri Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2026)
Inclusive learning​ is one of the solutions in the middle diversity ability students at school especially in field literacy and numeracy. Knowledge, ability, behavior behavior and required character​ student for use mathematics in more context​ wide including in literacy numeracy. Ability education counting hold role fundamental in improvement mathematics later​ day. This capacity covers ability understand and control number Good in a way symbolic or non- symbols. The purpose of study This is for know problem literacy and numeracy What only faced​ students. Research This use method study descriptive qualitative. Source information used​ in exam This is information choice start from notebook​​ daily, and relevant articles. Findings study This show that literacy character and skills numeracy can Work The same for strengthen One each other. Absence character can influence achievement domination ability education counting. Discipline and honesty, for example, can help child easier understand draft literacy and numeracy. Result of study This can utilized for future scientists​ for to unravel need in creation of learning models, modules learning for students and books guide for educators who can grow ability numeracy and character student.